Chytrid fungus infections in laboratory and introduced Xenopus laevis populations: assessing the risks for U.K. native amphibians - Tinsley, Richard C. (Biol Conserv, 2015)
The chytrid fungus Batrachochytrium dendrobatidis (Bd) is notorious amongst current conservation biology challenges, responsible for mass mortality and extinction of amphibian species. World trade in amphibians is implicated in global dissemination. Exports of South African Xenopus laevis have led to establishment of this invasive species on four continents. Bd naturally infects this host in Africa and now occurs in several introduced populations. However, no previous studies have investigated transfer of infection into co-occurring native amphibian faunas. A survey of 27 U.K. institutions maintaining X. laevis for research showed that most laboratories have low-level infection, a risk for native species if animals are released into the wild. RT-PCR assays showed Bd in two introduced U.K. populations of X. laevis, in Wales and Lincolnshire. Laboratory and field studies demonstrated that infection levels increase with stress, especially low temperature. In the U.K., native amphibians may be exposed to intense transmission in spring when they enter ponds to spawn alongside X. laevis that have cold-elevated Bd infections. Exposure to cross-infection has probably been recurrent since the introduction of X. laevis, >20 years in Lincolnshire and 50 years in Wales. These sites provide an important test for assessing the impact of X. laevis on Bd spread. However, RT-PCR assays on 174 native amphibians (Bufo, Rana, Lissotriton and Triturus spp.), sympatric with the Bd-infected introduced populations, showed no foci of self-sustaining Bd transmission associated with X. laevis. The abundance of these native amphibians suggested no significant negative population-level effect after the decades of co-occurrence.